PENERAPAN METODE GROUP INVESTIGATION (GI) TERHADAP MOTIVASI BELAJAR MAHASISWA SEMESTER II DALAM PEMBELAJARAN ILMU DASAR KEPERAWATAN: Application of Group Investigation Method To Learning Motivation of Second-Semester Students In Learning Basic Nursing Sciences - Tiara Putri Ryandini; Moh. Ubaidillah Fiqih; Dyah Pitaloka; Feby Lutfiatur Rosda (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
Based on the conditions experienced by the second-semester students of the Nursing Undergraduate Study Program at IIK NU Tuban, shows that motivation and learning outcomes are still low and tend to be less than optimal. One of the main causes is boredom. It's not boring teaching material, it's just that the lecturers are still not able to apply the models, strategies, methods, and learning media or approaches used. Efforts made by researchers to increase learning motivation are by applying Group Investigation (GI) learning techniques. With the application of this method, it is hoped that lecturers, students, and researchers will be able to determine the effectiveness of the Group Investigation (GI) method in increasing learning motivation for second-semester students in Learning Basic Nursing Sciences at IIK NU Tuban. This study used a pre-experimental design, with a one-group pre-test and post-test design. The sampling method used total sampling with a total of 139 respondents. The instruments used are SOPs and questionnaire sheets. The observation sheet is used to determine whether the GI method can be carried out according to the SOP. Data analysis used the Wilcoxon statistical test with SPSS 26. The results of the statistical test obtained Asymp. Sig. (2-tailed) p = 0.000 where the value of p < (0.000 < 0.05) then H1 is accepted, which means that there is an effect of the application of the Group Investigation (GI) Method on the Learning Motivation of Semester II Students in IDK Learning at IIK NU Tuban. Based on these results, it can be concluded that the application of the Group Investigation (GI) method can increase the learning motivation of second-semester students in IDK learning at IIK NU Tuban.